Corticosteroids for the treatment of respiratory infection by Mycoplasma pneumoniae in children: a cost-utility analysis - Buendía, JA; Patiño, DG (Wiley, 2023)
Introduction Increasing evidence has demonstrated the effectiveness and safety of corticosteroids in community-acquired pneumonia in children. More economic evaluations incorporating the new evidence and in the pediatric population are needed to know the efficiency of this treatment. This study aimed to evaluate the cost utility of the use of corticosteroids as adjuvant treatment for children with Mycoplasma pneumonia.